Synthesis and Characterization of Silica Gel from Palm Shell and Coir Ash - Sunarti, Sunarti; Mariwy, Abraham; Laitupa, Asasa N. (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2023)
This study aims to determine the composition of the oxide, the characteristics of palm shell and coir, and silica gel synthesized. The oxide composition, crystallinity, palm shell and coir ash functional groups were analyzed using XRF, XRD, and FTIR. Analysis of the functional groups and crystallinity using FT-IR and XRD. The results showed the composition of SiO2 in palm shell and coir ash was 76%, and SiO2 in the form of quartz and cristobalite was more dominant than amorphous SiO2. The synthesis success was indicated by the appearance of peaks with low intensity, not sharp, and resembling bumps on the synthesized silica gel diffractogram, which is an amorphous SiO2 characteristic. This result is confirmed by FT-IR, where absorption at wave number 455 cm-1 is a Si-O-Si bending vibration, 783 cm-1 is a stretching vibration of Si-O symmetry of Si-O-Si, 3454.51 cm-1, and 3568 cm-1 with fairly high intensity are characteristic of the -OH group from Si-OH. The wide and sharp absorption at 1083.99 cm-1 is a stretching vibration of the Si-O symmetry of Si-O-Si, 1625.99 cm-1 is -OH vibration of water molecule, 798.53 cm-1 is Si-O stretching vibration of Si-O-Si and absorption of 462.92 cm-1 indicates bending vibration of Si-O-Si.